Passenger Car Equivalents for Heavy Vehicles at Roundabouts. a Synthesis Review - Giuffrè, Orazio; Granà, Anna; Giuffrè, Tullio; Tumminello, Maria Luisa; Acuto, Francesco (Frontiers in Built Environment, 2019)
Passenger Car Equivalents (PCEs) are used to convert a mixed traffic flow into an equivalent passenger car flow and to analyze capacity and level-of-service of roads and intersections. Most roundabouts guidelines propose constant values for PCEs but a single PCE value can result improper under heterogeneous traffic conditions. PCEs should be vary with traffic and road conditions so that PCEs used under undersaturated conditions may underestimate the effect of heavy vehicles or be not sensitive to the traffic level or characteristics of heavy vehicles. Compared to other at-grade intersections, the interaction between the operational performances of the heavy vehicles and the geometric features at roundabouts can produce significant impacts on the heavy vehicle paths and traffic operations due to the curvilinear nature of the roundabout design. Literature presents various estimation methods to obtain PCE values for heavy vehicles. The focus of this paper is to review statistical methods and traffic simulation studies based on microscopic approaches used to calculate PCEs for heavy vehicles driving roundabouts. Effects on capacity and PCE estimations based on models currently employed in roundabout analysis are also compared. The results obtained in this study aim at providing an overview of the existing knowledge concerning the estimation of PCEs at roundabouts and can represent a guideline for transportation engineers in the design and capacity analysis of roundabouts where mixed traffic conditions occur.